Sirt6 regulates lifespan in Drosophila melanogaster. - Taylor, J.R.; Wood, J.G.; Mizerak, E.; Hinthorn, S.; Liu, J.; Finn, M.; Gordon, S.; Zingas, L.; Chang, C.; Klein, M.A.; Denu, J.M.; Gorbunova, V.; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2022)
Sirt6 is a multifunctional enzyme that regulates diverse cellular processes such as metabolism, DNA repair, and aging. Overexpressing Sirt6 extends lifespan in mice, but the underlying cellular mechanisms are unclear. Drosophila melanogaster are an excellent model to study genetic regulation of lifespan; however, despite extensive study in mammals, very little is known about Sirt6 function in flies. Here, we characterized the Drosophila ortholog of Sirt6, dSirt6, and examined its role in regulating longevity; dSirt6 is a nuclear and chromatin-associated protein with NAD+-dependent histone deacetylase activity. dSirt6 overexpression (OE) in flies produces robust lifespan extension in both sexes, while reducing dSirt6 levels shortens lifespan. dSirt6 OE flies have normal food consumption and fertility but increased resistance to oxidative stress and reduced protein synthesis rates. Transcriptomic analyses reveal that dSirt6 OE reduces expression of genes involved in ribosome biogenesis, including many dMyc target genes. dSirt6 OE partially rescues many effects of dMyc OE, including increased nuclear size, up-regulation of ribosome biogenesis genes, and lifespan shortening. Last, dMyc haploinsufficiency does not convey additional lifespan extension to dSirt6 OE flies, suggesting dSirt6 OE is upstream of dMyc in regulating lifespan. Our results provide insight into the mechanisms by which Sirt6 OE leads to longer lifespan.